Qur’anic Education Curriculum Management to Enhance Early Childhood Learning in Indonesia - Mursal Aziz; Muhammad Hasbie Ashshiddiqi; Harmayani (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2026)
This study aims to analyze the implementation of the Al-Quran education curriculum management in optimizing early childhood learning at Aisyiyah Bustanul Athfal (ABA) I Kindergarten, Aek Kanopan Timur, North Labuhanbatu. This study uses a qualitative approach with a case study type, involving the principal, teachers, students, and parents as informants. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation, while data analysis used data condensation techniques that included selecting, focusing, and simplifying data to draw conclusions. The results of the study indicate that the implementation of curriculum management has been carried out regularly through planning (annual, semester, and weekly programs), the implementation of play-based learning approaches with varied methods, and continuous authentic evaluation. This implementation has a positive impact on improving the ability to read hijaiyah letters, memorize short verses, and children's interest and love for the Al-Quran. However, there are obstacles in the form of differences in children's abilities, limited infrastructure, and suboptimal parental support. Therefore, this study recommends strengthening collaboration between schools and parents, improving teacher competency, and developing innovative media and technology-based learning methods to support the optimization of Qur'an learning in early childhood.